(untitled) (Journal of Fiber Bioengineering and Informatics, 2010)
With the help of electronic microscope and scanning electronic microscope, profiled polyester fibers with cross section shapes like “Y”, “+” and “C” were analyzed individually. Four kinds of single and double-faced knitted fabrics with different structures and density were manufactured with the profiled polyester fibers, and their wicking height, water retention and drying efficiency were investigated individually. It was found that the more abnormal the fiber cross section is, the better is the moisture-transfer and fast drying properties of its fabrics.